2008
DOI: 10.1007/s10552-008-9153-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in hormone metabolizing genes and risk of testicular germ cell tumors

Abstract: Testicular germ cell tumors (TGCT) that arise in young men are composed of two histologic types, seminomas and nonseminomas. Risk patterns for the two types appear to be similar and may be related to either endogenous or exogenous hormonal exposures in utero. Why similar risk patterns would result in different histologic types is unclear, but could be related to varying genetic susceptibility profiles. Genetic variation in hormone metabolizing genes could potentially modify hormonal exposures, and thereby affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 55 publications
4
33
0
1
Order By: Relevance
“…Recent evidence supports an association of TGCT with polymorphisms in these genes: we and others have reported an association with CAG/GGN repeat length of the androgen receptor gene (Giwercman et al 2004, Garolla et al 2005 and with FSH receptor gene polymorphisms (Ferlin et al 2008a), and an association with some maternal and/or offspring hormonemetabolizing genes of the cytochrome P450 family (CYP1A1, CYP1A2, CYP3A4, and CYP3A5) has been suggested (Starr et al 2005, Figueroa et al 2008.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Recent evidence supports an association of TGCT with polymorphisms in these genes: we and others have reported an association with CAG/GGN repeat length of the androgen receptor gene (Giwercman et al 2004, Garolla et al 2005 and with FSH receptor gene polymorphisms (Ferlin et al 2008a), and an association with some maternal and/or offspring hormonemetabolizing genes of the cytochrome P450 family (CYP1A1, CYP1A2, CYP3A4, and CYP3A5) has been suggested (Starr et al 2005, Figueroa et al 2008.…”
Section: Introductionsupporting
confidence: 55%
“…We did not include CYP3A4 and CYP3A5 genes in our screening, nor we included SNPs rs4886605 and rs2606345 in CYP1A1 and rs762551 in CYP1A2; therefore, we were unable to confirm such associations. On the contrary, Figueroa et al (2008) also studied the HSD17B4 gene and they found no association with TGCT; however, SNP rs11205 that we found differently distributed between cases and controls was not included in their study. Taken together these results, although not definitive, strongly suggest that steroid hormone metabolism genes might modulate the susceptibility to TC.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, collective evidence from the descriptive literature and marked inconsistencies between analytic studies distinguishing seminomas from nonseminomas indicate that either they are etiological rather than homogeneous, or some heterogeneity exists but the dichotomization is etiologically irrelevant. The findings of gene association studies also suggest that nonseminomas may be worth further investigating for genetic susceptibility (38)(39)(40)(41)(42). As nonseminomas comprised diverse subtypes, analysis of nonseminomas by its subtypes may help us to clarify the gene-environment interaction in the etiology of testicular cancer, but few studies will have sufficient numbers for further differentiation.…”
Section: Discussionmentioning
confidence: 99%